Status of the Electromagnetic Calorimeter Trigger system at the Belle II experiment. (7th September 2017) - Kim, S.H.; Lee, I.S.; Unno, Y.; Cheon, B.G.
Abstract: The Belle II experiment at the SuperKEKB collider in Japan has been under the construction toward a physics run in 2018 with an ultimate target of 40 times higher instantaneous luminosity than the KEKB collider. The main physics motivation is to search for the New Physics from heavy quark/lepton flavor decays. In order to select an event of interest efficiently under much higher luminosity and beam background environment than the KEKB, we have upgraded the Electromagnetic Calorimeter (ECL) hardware trigger system. It would be realized by the improvement of ECL trigger logic based on two main triggers, the total energy and the number of clusters, with an FPGA-based flexible architecture and a high speed serial link for the data transfer. We report the current status of hardware, firmware, and software that has been achieved so far. The overall scheme of the system will be presented as well.